An anesthesiologist‐led inpatient buprenorphine initiative. Issue 6 (10th March 2021) - Patel, Nisarg; Schwenk, Eric S.; Ferd, Polina; Torjman, Marc C.; Baratta, Jaime L.; Viscusi, Eugene R.
Abstract: Hospitalized patients with opioid use disorder who present with acute pain are challenging to manage. Without any treatment, their mortality in the first 28 days after discharge is substantially increased. Unlike extended‐release naltrexone, which requires a period of withdrawal, or methadone, which can cause prolonged corrected QT (QTc) and carries a higher risk of respiratory depression, buprenorphine provides potent analgesia with low respiratory risk. Hospitalization provides a unique opportunity for clinicians to perform buprenorphine induction, which could potentially reduce mortality without affecting analgesia. Our acute pain management service uses multimodal analgesia to maintain adequate analgesia and minimize withdrawal during buprenorphine induction in the hospital. With the assistance of narcotics addiction rehabilitation program specialists, we help link patients to outpatient buprenorphine providers and maximize the chance of successful recovery. The primary outcome of this study was to determine the percentage of patients who filled an outpatient buprenorphine prescription after undergoing inpatient induction.